Metabolomic disorders caused by an imbalance in the gut microbiota are associated with central precocious puberty - Liu, Chunjie; Zhou, Shasha; Li, Yan; Yin, Xiaoqin; Li, Pin (Frontiers in Endocrinology, 2024)
ABSTRACT Background: Central precocious puberty (CPP) is characterized by the premature activation of the hypothalamic-pituitary-gonadal axis, resulting in early onset of sexual development. The incidence of CPP has been rising in recent years, with approximately 90% of cases lacking a clearly identifiable etiology. While an association between precocious puberty and gut microbiota has been observed, the precise causal pathways and underlying mechanisms remain poorly understood. The study aims to investigate the potential mechanisms through which gut microbiota imbalances may contribute to CPP. Methods: In this study, clinical information and fecal samples were collected from 50 CPP patients and 50 healthy control subjects. The fecal samples were analyzed by 16S rDNA sequencing and UPLC‒MS/MS metabolic analysis. Spearman correlation analysis was used to identify the relationships between gut microbiota and metabolites. Results: The gut microbiota composition in CPP patients was significantly different from that in healthy controls, characterized by an increased abundance of Faecalibacterium and a decreased abundance of Anaerotruncus. Additionally, significant differences were observed in metabolite composition between the CPP and control groups. A total of 51 differentially expressed metabolites were identified, with 32 showing significant upregulation and 19 showing significant downregulation in the CPP group. Furthermore, Spearman correlation analysis indicated that gut microbiota dysbiosis may contribute to altered metabolic patterns in CPP, given its involvement in the regulation of several metabolic pathways, including phenylalanine and tyrosine biosynthesis and metabolism, the citrate cycle (TCA cycle), glyoxylate and dicarboxylate metabolism, and tryptophan metabolism. Conclusions: The study revealed the gut microbial and metabolite characteristics of CPP patients by integrating microbiome and metabolomics analyses. Moreover, several key metabolic pathways involved in the onset and progression of CPP were identified, which were regulated by gut microbiota. These findings broaden the current understanding of the complex interactions between gut microbial metabolites and CPP, and provide new insights into the pathogenesis and clinical management of CPP.